1994
DOI: 10.1029/93wr02402
|View full text |Cite
|
Sign up to set email alerts
|

Injection‐attachment of Methylosinus trichosporium OB3b in a two‐dimensional miniature sand‐filled aquifer simulator

Abstract: For some potentially useful and emerging in situ bioremediation technologies it is important to control bacterial attachment to subsurface materials during the injection of microbial cell suspensions. In this study the attachment patterns of Methylosinus trichosporium OB3b were measured after horizontal injections into a two-dimensional miniature aquifer simulator containing a wet homogeneous sand. In preliminary sand column assays, bacterial attachment to the sand was increased nearly 2 orders of magnitude co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 38 publications
2
40
0
Order By: Relevance
“…The effect had [119,98], analyzing earlier breakthrough of microbes relative to a tracer, assigned a lower dispersivity for microbes than for solutes. They noted differences in dispersion that led to faster breakthrough, although they were unable to pinpoint the mechanism that caused these differences.…”
Section: Advection Diffusion Dispersionmentioning
confidence: 98%
“…The effect had [119,98], analyzing earlier breakthrough of microbes relative to a tracer, assigned a lower dispersivity for microbes than for solutes. They noted differences in dispersion that led to faster breakthrough, although they were unable to pinpoint the mechanism that caused these differences.…”
Section: Advection Diffusion Dispersionmentioning
confidence: 98%
“…Size exclusion effects have been observed in laboratory columns [37,92,114,156,164] and in field experiments [50,172,189]. Exclusion is a phenomenon where transported particles move faster than the mean pore-water velocity, and involves an increase in the transport rate due to the size or charge of the material conveyed.…”
Section: Size Exclusionmentioning
confidence: 99%
“…Engfield and Bengtsson [37] examined the effects of unaccounted exclusion on the effective value of partition coefficients for macromolecular transport, and Shonnard et al [114] analyzed early breakthrough of microbes relative to phenol red in a capillary in the context of Taylor-Aris dispersion theory [181]. Shonnard et al [114] assign the microbe a lower radial diffusivity than a molecular solute so that the microbial transport is dominated by convection, on the basis of which they use the high Peclet limit solution of the capillary convection-dispersion equation. This approach is critiqued in Ginn [45].…”
Section: Size Exclusionmentioning
confidence: 99%
“…Effects of cell surface heterogeneity [Simoni et al, 1998] and motile/ nonmotile cells [Camesano and Logan, 1998] on cell attachment in column studies have been recently reported. Studies of microbial attachment in a two-dimensional (2-D) miniature sand-filled aquifer simulator [Shonnard et al, 1994] and a biofilter [Taylor et al, 1993] are reported. Harvey et al [1989] have reported field research on the transport of bacteria in a sandy aquifer.…”
Section: Prior Experimental Approachesmentioning
confidence: 99%